Inhibition of Streptococcus mutans, antioxidant property and cytotoxicity of novel nano-zinc oxide varnish - Barma, Manali Deb; Muthupandiyan, Indumathy; Samuel, Srinivasan Raj; Amaechi, Bennett T. (Archives of oral biology, 2021)
•Zinc-oxide nanoparticles (ZnO-NP) effectively inhibits S. mutans growth at 0.53 μg/mL.•ZnO-NP showed anti-biofilm, acid-inhibiting and anti-oxidant properties.•ZnO-NP varnish has anti-caries potential for being antimicrobial against S. mutans. Zinc is a potent antimicrobial against cariogenic bacteria and effective anti-plaque agent. The present study investigated the efficacy of zinc oxide nanoparticles (ZnO-NP) varnish to inhibit S. mutans growth, biofilm, acid production, and its antioxidant potential and cytotoxicity. Green synthesized ZnO-NP were characterized using ultraviolet–visible spectroscopy, x-ray diffraction spectroscopy, and transmission electron microscopy. Secondary metabolites were assessed using fourier transform infrared spectroscopy. Anti-oxidant potential was ascertained using 2,2-diphenyl-2-picrylhydrazyl hydrate (DDPH) assay and cytotoxicity of synthesized nanoparticles was evaluated on human liver cancer (Hep G2) and human embryonic kidney 293 (HEK-293T) cell lines. Synthesized ZnO-NP showed excellent antimicrobial properties against S. mutans, as the minimum inhibitory and bactericidal concentrations were 0.53 μg/mL, and 1.3 μg/mL respectively. ZnO-NP at 0.1 mg/μl concentration had the greatest zone of inhibition (24 mm), followed by 0.05 mg/μl ZnO-NP (23 mm) and 0.05 mg/μl ampicillin (21 mm). Further, 0.1 mg/μl ZnO-NP varnish inhibited 90 % of S. mutans biofilms and reduced 24 h acid production closest to that of baseline and it also exhibited antioxidant capacity in a dose dependent manner (94 % inhibition-100 μg/mL). Biocompatibility of ZnO-NP varnish was evaluated on Hep G2 and HEK-293T cell lines; and the highest concentration of 0.1 mg/μl ZnO-NP used caused very low cytotoxicity to Hep G2 cells and was non-cytotoxic to HEK-293T cells. Within the limits of this study, ZnO-NP varnish was effective in inhibiting S. mutans and holds great potential as an effective anticaries agent.